Retrospectively analysis of Pathological features of 1047 cases of Thyroid Nodules - Xing, Zhao; Gang, Zhang (Asian Journal of Medical Sciences, 2019)
Background: In recent years, the incidence of thyroid cancer is on the rise, almost become one of the fastest-growing malignant tumor, especially in women. The reasons of the incidence of thyroid, is not only the use of detection means. The relationship between clinical pathological characteristics and prognosis of thyroid is controversial. Aims and Objective: One thousand forty seven cases of thyroid nodule (thyroid nodules, TN) were retrospectively analyzed, to study the distribution of TN and its clinical pathological features. Materials and Methods: Clinicopathological data of 1047 cases TN were retrospectively studied, from Chengde Medical College Affiliated Hospital and (10.2017 to 08.2018) Chengde County Hospital (01. 2016 to 08.2018), χ2 test is used to analyze the relationship between clinical pathologic factors and lymph node. Results: In 1047 cases of TN, nodular goiter 50.62%, Hashimo-to’s thyroiditis 3.34%, thyroid carcinomas 32.28%,thyroid adenoma 10.12%, toxic nodular goiter 0.29%. The lymph node metastasis positive rate was higher in <45 years of age and tumor diameter >1 cm of the thyroid carcinoma patients. Gender, whether single had no relation with occurrence of neck lymph node metastasis. Conclusion: The lymph node metastasis positive rate is higher in <45 years of age and tumor diameter greater than 1 cm of the thyroid carcinoma patients.